CEREBRAL AUTOREGULATION IN HEAD INJURY - Ni Made Ayu Apsari Dewi (Universitas Udayana, 2013)
A characteristic feature of the cerebral circulation is that the cerebral blood flow is dynamically adjusted to protect brain blood from changes in perfusion pressure. Cerebral blood flow tends to remain constant over a range of systemic blood pressures (cerebral auto regulation). Increases and decreases of the arterial CO2 tension (PaCO2) will increase and decrease cerebral blood flow by cerebral vasodilatation and vasoconstriction, independent of cerebral auto regulation (CO2 reactivity of the brain). After brain injury, cerebral flow auto regulation gets impaired in most patients. In patient with severe traumatic brain injury, impaired CO2 reactivity occurred in early stage trauma.